Negotiation : Strategies for Mutual Gain. - Hall, Dr. Lavinia (SAGE Publications, 1992)
With contributions from top scholars in the field of negotiation, this clear and entertaining volume effectively blends technique with theory to present frameworks for effective negotiating, analyses of person-to-person negotiating situations and applications in organizational settings. Building on the concept that conflict, when managed well, can provide the impetus for growth, constructive change and mutual benefit, the book is dedicated to breaking the paradigm of winning and losing and transforming negotiation into a search for improved solutions to problems.